Женщина-загадка: роман / Марша Ловелл - Ловелл Марша (Панорама романов о любви, 2005)
Экземпляры: (20211020) / Инвентарный номер: 31460 / Цена: 18.00 / Сис.шифр: 84(4Вел) / Авт.знак: Л 68 / ГРНТИ: 17.82 / ББК: 84(4Вел)